NILAI-NILAI PENDIDIKAN DALAM PERMAINAN SHOGI - Ihsan, Muhammad Muhtadi; Haryanti, Pitri (Mahadaya: Jurnal Bahasa, Sastra, Dan Budaya, 2023)
This study aims to determine the educational values ​​that exist in Shogi. This research was conducted using a descriptive research method with a qualitative approach, by documenting various kinds of data in observations from youtube, articles, journals, online books, and information from the internet, then summarized specifically and in detail based on what was researched. The results of this study prove that shogi has educational values ​​with the roles that exist in shogi that strengthen research by producing good characters in socializing, having high concentration, strengthening social relations both in the family and in public places, and also obeying rule. Keywords: Shogi, Education, Positive Influence, Japan.